2011
DOI: 10.1111/j.1440-1746.2010.06435.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and pathogenesis of gallbladder cancer

Abstract: The results revealed that H. pylori was present in a large population, including both GBC and GSD patients, which indicates its endemic presence in the Varanasi region. Thus, it appears H. pylori might not have a significant role in the etiopathogenesis of GBC in our region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 43 publications
(57 reference statements)
1
36
0
Order By: Relevance
“…The accuracy of the 26KDa primer is 9.3 % compared to that of 11.6 % using the Ure A gene on the same samples. Mishra and others [2] recently reported that 42.5 % of gallbladder carcinoma tissues were positive for the HSP60 gene. Bansal et al [12] based the PCR on the UreA gene of H. pylori.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…The accuracy of the 26KDa primer is 9.3 % compared to that of 11.6 % using the Ure A gene on the same samples. Mishra and others [2] recently reported that 42.5 % of gallbladder carcinoma tissues were positive for the HSP60 gene. Bansal et al [12] based the PCR on the UreA gene of H. pylori.…”
mentioning
confidence: 94%
“…BostanoAylu et al [1] could not culture Helicobacter in any of their 47 patients with gallstone disease and 30 controls. However, Mishra et al [2] recently demonstrated positive culture in 30 % patients of gallstone disease and 44 % gallbladder cancer specimens.…”
mentioning
confidence: 99%
See 3 more Smart Citations